Growth Response of Hydroponic Rice Seedlings at Elevated Concentrations of Potassium Chloride - Shaibur, MR; Shamim, AHM; Kawai, S (Journal of Agriculture & Rural Development, 2008)
Â A hydroponic experiment was conducted in the greenhouse to observe the effect of potassium chloride (KCl) on growth, macro elements and sodium (Na) concentration of rice seedlings (Oryza sativa L. cv. Hitomebore). The plants were grown up to 14 days after treatments (DAT) treated with 0, 10, 20 and 30 mM KCl. Shoot dry weight (dw) decreased significantly in the 10 mM KCl treatment, indicated that rice seedlings were highly sensitive (glycophytes) to KCl. However, root dw increased in the 10 mM KCl treatment as compared to other treatments, indicated that KCl could enhance root dw at lower concentration. The result indicated that the shoot of rice seedlings was highly sensitive to KCl than that of root. Shoot height, root length and leaf number decreased significantly in the 20 and 30 mM KCl treatments, while the width of leaf blade decreased significantly only in the 30 mM KCl treatment. Considering 10% dw reduction the critical toxicity levels (CTL) of K in shoot was 60.4 mg g-1 dw and 23.3 mg g-1 dw in root. Potassium chloride decreased calcium (Ca), magnesium (Mg) and Na concentrations both in shoot and root, indicated that K had antagonistic relationships with Ca, Mg and Na in rice seedlings. Phosphorus (P) concentration decreased in shoot in the 30 mM KCl treatment indicated that the toxic effete of KCl on P. Potassium concentrations increased in shoot and root with the increasing KCl concentrations in the nutrient solution. The sensitivity response of the elements in rice was Na>Mg>Ca>P under elevated concentrations of KCl. Key words: Calcium, hydroponic, magnesium, potassium, potassium chloride, rice, sodium. doi:10.3329/jard.v6i1.1656 J Agric Rural Dev 6(1&2), 43-53, June 2008